Radiotherapy Increases aMMP-8-Levels and Neutrophil/Lymphocyte Ratio Rapidly in Head and Neck Cancer Patients: A Pilot Study - Brandt Ella; Keskin Mutlu; Tervahartiala Taina; Yılmaz Mustafa; Harmankaya İlknur; Karaçetin Didem; İpek Turgut; Gürsoy Ulvi Kahraman; Rautava Jaana; Gupta Shipra; Hagström Jaana; Räisänen Ismo T; et al. (Sage, 2025)
Radiotherapy for head and neck carcinoma (HNC) has both curative and palliative purposes. This study investigated mouthrinse aMMP-8 levels, molecular forms of MMP-8, blood neutrophil counts and neurophil/lymphocyte ratios before and 3 weeks after HNC radiotherapy started. Thirteen HNC patients undergoing radiotherapy were included. Mouthrinse samples (before and 3 weeks after HNC radiotherapy had started) were assayed quantitatively by aMMP-8 point-of-care-kit (PerioSafe®/ORALyzer®) and by western immunoblot. Total neutrophil counts and neutrophil/lymphocyte ratios were evaluated in the hemogram results. Three weeks after HNC radiotherapy started, significant increases in aMMP-8 levels and neutrophil/lymphocyte ratios were observed. No significant difference was found in total neutrophil counts. Elevations of the activated and fragmented MMP-8 levels after HNC radiotherapy application were observed on western immunoblot analysis. The increase in the aMMP-8 levels and neutrophil/lymphocyte ratios indicate inflammation both locally and systemically suggesting increased risk for periodontitis due to the HNC radiotherapy.